Activation of the motor cortex during phasic rapid eye movement sleep. Issue 2 (18th January 2016) - De Carli, Fabrizio; Proserpio, Paola; Morrone, Elisa; Sartori, Ivana; Ferrara, Michele; Gibbs, Steve Alex; De Gennaro, Luigi; Lo Russo, Giorgio; Nobili, Lino
Abstract : When dreaming during rapid eye movement (REM) sleep, we can perform complex motor behaviors while remaining motionless. How the motor cortex behaves during this state remains unknown. Here, using intracerebral electrodes sampling the human motor cortex in pharmacoresistant epileptic patients, we report a pattern of electroencephalographic activation during REM sleep similar to that observed during the performance of a voluntary movement during wakefulness. This pattern is present during phasic REM sleep but not during tonic REM sleep, the latter resembling relaxed wakefulness. This finding may help clarify certain phenomenological aspects observed in REM sleep behavior disorder. Ann Neurol 2016;79:326–330